Pengaruh Corporate Governance dan Struktur Modal Terhadap Kinerja Keuangan - Ikhlas Fitri Edi Rahmah; Selvia Anggi Anggraeni; Fil Isnaeni (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the influence of Corporate Governance and capital structure on the company's financial performance by focusing on two main governance variables, namely managerial ownership and institutional ownership. The research approach used is qualitative with the type of library research. Data was obtained from various secondary sources such as books, national and international journals, and scientific repositories accessed through Google Scholar, Mendeley, and Garuda. The analysis was carried out in a descriptive-analytical and comparative manner, by examining the results of previous research on the relationship between variables. The results of the study show that managerial ownership has a positive effect on financial performance through the alignment effect mechanism between managers and shareholders. However, at a level of ownership that is too high, there is a negative effect (entrenchment effect) that can reduce the company's performance. Institutional ownership serves as an effective external oversight mechanism, where the proportion of ownership by financial institutions is able to improve managerial discipline and transparency. However, its influence depends on the level of active involvement of institutional investors in corporate supervision. Meanwhile, the capital structure has a varied influence on financial performance. The proportionate use of debt can increase profitability through tax efficiency and financial discipline, but excessive use of debt actually reduces performance due to increased financial risks. In general, the relationship between Corporate Governance, capital structure, and financial performance is complex and contextual, influenced by industry characteristics, company size, and ownership structure. The study concludes that the improvement of financial performance is not only determined by financial policies, but also by the effectiveness of governance and the balance of ownership structures. The results of this study provide theoretical implications for the development of agency theory and trade-off theory, as well as practical recommendations for companies to design more efficient and sustainable governance and financing policies.